PERAN PENGETAHUAN DAN PROSES BELAJAR TERHADAP PERUBAHAN STRATEGI PRAKTEK BISNIS: SEBUAH ANALISIS WACANA TENTANG PERUBAHAN IKLIM - Elvy Maria Manurung (Bina Ekonomi, 2011)
Flooding and landslides are now beginning to be a daily sight in many areas in Indonesia. What recently happened, and quite terrifying is, the loss (drop down) street in the capital-city. Rainfall in some cities, seem evenly throughout the year. Geographical circumstances of Indonesian as an island Country looks began to change. Land start to shrinking white the ocean's broadening. The impact of this environment and natural changes, such as climate change, would certainly affect people’s lives. Disadvantages socially and economically will reduce the level of public welfare in general. This, in turn, will impact on business practices that had been occupied by businessmen. Willy-nilly, like it or 'not, they must begin to take into account the reality on the surrounding environment. The spread of knowledge through the media should respond by updating the values (corporate-value) that had been possessed by the company,  learning how to change,  and  formulate a new one.